Pelatihan Sistem Informasi E-Commerce untuk Optimalisasi Proses Konsumen, Produksi, dan Pemasaran bagi Pelaku UMKM pada Sentra Industri Ayam Goreng Maju Makmur Kalasan Yogyakarta: E-Commerce Information System Training to Enhance Consumer, Production and Marketing Processes for MSMEs at the Maju Makmur Fried Chicken Industrial Center Kalasan Yogyakarta - Zaidir, Zaidir; Sujarweni, Veronika Wiratna; Erizal, Erizal (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
The e-commerce information system training program implemented at the Maju Makmur Kalasan Yogyakarta Fried Chicken Industry Center aims to improve the skills of MSMEs in consumer management, production, and marketing through technology. The evaluation of the effectiveness of the program showed a significant increase in the knowledge and skills of participants, which was reflected in better stock management, production efficiency, and marketing strategies. Compared to the previous approach that was less measurable, this evaluation used a more comprehensive method and showed stronger and more sustainable results. The results of this PkM activity can improve the skills and efficiency of MSMEs at the Maju Makmur Fried Chicken Industry Center. The training activity was not only successful in the short term, namely improving the technical skills of participants, but also long-term benefits by using a custom-made e-commerce information system so that it can encourage the growth and competitiveness of MSMEs.